Mechanisms of microRNA action in rectal cancer radiotherapy. Issue 17 (5th September 2022) - Zhu, Lili; Wang, Mojin; Chen, Na; Zhang, Yujie; Xu, Tao; Zhuang, Wen; Xiao, Shuomeng; Dai, Lei
Abstract : Abstract: Preoperative neoadjuvant chemoradiotherapy, combined with total mesorectal excision, has become the standard treatment for advanced localized rectal cancer (RC). However, the biological complexity and heterogeneity of tumors may contribute to cancer recurrence and metastasis in patients with radiotherapy-resistant RC. The identification of factors leading to radioresistance and markers of radiosensitivity is critical to identify responsive patients and improve radiotherapy outcomes. MicroRNAs (miRNAs) are small, endogenous, and noncoding RNAs that affect various cellular and molecular targets. miRNAs have been shown to play important roles in multiple biological processes associated with RC. In this review, we summarized the signaling pathways of miRNAs, including apoptosis, autophagy, the cell cycle, DNA damage repair, proliferation, and metastasis during radiotherapy in patients with RC. Also, we evaluated the potential role of miRNAs as radiotherapeutic biomarkers for RC.